Visibility of alcohol and other drug subjects and careers provided by Australian social work programs - Fischer, Jane Anne; Thompson, Kirrilly; Muminovic, Armin; McLaren, Helen (Journal of social work practice in the addictions, 2025)
Higher education providers play an important role in equipping social work students with alcohol and other drug (AOD) related knowledge, attitudes and skills to help them support clients. They also play a role in promoting awareness of AOD-related career pathways. A scoping review of the websites of sixty-three accredited pre-service social work degree programs in Australia found that nine (14%) programs offered explicit AOD-related subjects (n = 11) and 12 (19%) programs referenced AOD-related careers. These findings suggest that many social work graduates may be inadequately prepared to support clients with AOD issues. A specialist AOD credential or program could increase knowledge and skills and promote awareness of AOD-related careers for social workers, but should not detract from the relevance of AOD-related content at an undergraduate level. This study establishes the need for primary research with graduates to determine their AOD-related knowledge, attitudes, and skills.